The Relationship between Electricity Consumption and Economic Growth: Evidence from Azerbaijan - Humbatova, Sugra Ingilab; Ahmadov, Fariz Saleh; Seyfullayev, İlgar Zulfigar; Hajiyev, Natig Gadim-Ogli (International Journal of Energy Economics and Policy, 2019)
Research examines the relations between GDP in Manat and Dollar and total electric energy consumption (1995-2017) for the last 22 years in the Republic of Azerbaijan. Besides, the relations between the electric energy consumption and the growth of GDP in these sectors were analysed. Autoregressive distributed lag model was used as a research methodology. Stationary tests of variables (ADF, PP, and KPSS) and Pairwise Granger Causality Tests were done. Stability of models was examined. Eviews_9 econometric software program was used to establish graphics and do calculations. Having analysed the research, there is a positive correlation not only in GDP and electric energy consumption but also electric energy consumption and GDP in different sectors of economy. We recommend to save electric energy. Keywords: Electric Energy Consumption, GDP Growth, Autoregressive Distributed Lag JEL Classifications: F15, B28, C23, Q43, O52 DOI: https://doi.org/10.32479/ijeep.8642